BASIC CONCEPTS proxy - Yuce Yuliani (JAKSTIK Journal, 2006)
In a network of intermediaries required, one form of such intermediaries is Proxy. Proxies can be understood as a third party who stood in the middle between two parties that are interconnected and function as an intermediary, such that the first party and second party not directly related, but each dealing with an intermediary, namely a proxy.   As an illustrative example: If a student borrows a book in the library, sometimes the students were not allowed to directly search and retrieve their own books that we want from the bookcase, but students asked for the book to the officers and of course by giving a number or code book that he wanted, and then the officer who will find and fetch the book. In the case above, the librarian has acted as an intermediary or proxy. Officers are also able to ensure and maintain, for example, so that students can only borrow books for students, lecturers can borrow books of all books, or the general public may only borrow a specific book.  Maybe the process takes more time than if we directly search and retrieve their own books we want. But if only every time officers locate and retrieve a book for someone, the officer also made several copies of the book before giving his book to people who ask, and keep it on the table service, so if there are other people who request a specific book, a very big possibility The requested book has been available a copy of it on a table, and the clerk gave it to stay straight. The result is a faster service and better security as well.   The above description explains the concept and basic functions of a proxy in the computer network and internet communications. Proxy servers have three main functions namely Connection Sharing, Filtering and Caching. Each function will be described further below.